(untitled) (Research, Society and Development, 2022)
The city of Recife is one of the largest historical and cultural centers in Brazil, with multiple historical buildings important for the conservation of Pernambuco’s culture. The Museum of Archeology and Natural Sciences of UNICAP is one of these buildings that continue to preserve the history of the state of Pernambuco, but the building currently has significant levels of pathological manifestations that are threatening the longevity of the structure. Therefore, the development of this work aims to be a concise document, analyzing all the pathological manifestations present in the structure during the research period, recording the accumulation of manifestations and preparing damage maps referring to the four main facades, for an easy visualization of the problem. For the beginning of the research, multiple visits were made to the museum, in which a visual inspection with a photographic camera was carried out. Then, the manifestations were identified through a literary review in online databases and their causes described in the report. Finally, it proceeded with the lifting of the facades in Autocad and the representation of the pathological manifestations on them. The research result demonstrates a high concentration of pathological manifestations present on all facades, demonstrating a lack of maintenance visible to everyone who passes through the museum. The need for maintenance is apparent and with pathological manifestations that threaten the structural stability of the museum, increasing severity. A facade repair project is needed before the damage forces a modernization of the structure and the loss of a cultural center in Pernambuco.